Prognostic risk factors for complications associated with Tibiotalocalcaneal fusion with a nail. Issue 3 (14th September 2018) - Callahan, Ryan; Aynardi, Michael; Walley, Kempland; Saloky, Kaitlin; Juiano, Paul
Category: Ankle Introduction/Purpose: Tibiotalocalcaneal (TTC) fusion with a nail is an effective salvage procedure for several foot and ankle pathologies, but it is associated with a relatively high complication rate and often performed on patients with multiple medical comorbidities. There is a paucity of literature that aids in predicting outcomes for patients undergoing TTC fusion with a nail. Methods: Clinical and radiographic outcomes for 82 patients from 2012-2016 who underwent TTC fusion with intramedullary nailing were retrospectively evaluated. Postoperative complications of nonunion, infection, reoperation, and hardware failure were included for comparison. Patient dependent variables and surgeon dependent variables were evaluated for association with these postoperative complications. Results: The overall complication rate for TTC fusion with a nail was 47/82 (57.3%). Diabetes (p=.049), diabetic neuropathy (p=.031), ASA classification (p=.005), and Charcot neuropathy (p=.003) were associated with nonunion of either the tibiotalar or subtalar joints in 29/82 (35.3%) patients. Diabetic neuropathy was associated with need for reoperation (p=.016) in 21/82 (25.6%) patients. Diabetic neuropathy (p=.022) and HbA1C >7.5 (p=.047) was associated with hardware failure in 13/82 (15.9%) patients. The odds ratio (OR) for diabetic neuropathy was 2.99 (p=0.038) for nonunion in the tibiotalar or subtalar joints, 3.46 (p=0.021) for re-operation, and 4.11 (p=0.035) for hardware failure. High ASA classification had an odds ratio of 3.93 (p=0.006) for nonunion in the tibiotalar or subtalar joints. Conclusion: Patients with diabetic neuropathy, Charcot neuropathy, elevated HbA1C, and higher ASA classification demonstrated a higher complication rate in patients undergoing TTC fusion with a nail.